2021
DOI: 10.18388/pb.2021_388
|View full text |Cite
|
Sign up to set email alerts
|

Post-translacyjne i post-transkrypcyjne mechanizmy regulacji aktywności hydroksylazy tyrozynowej w ośrodkowym układzie nerwowym-wpływ wysiłku fizycznego

Abstract: Liczne badania wskazują, że dopamina  (DA) jest ważnym regulatorem funkcji motorycznych, psychologicznych  i kognitywnych. Utrzymanie odpowiedniego stężenia DA jest warunkiem prawidłowego  działania tych funkcji.  W kontroli syntezy DA bierze udział hydroksylaza tyrozynowa (TH). Celem pracy niniejszej pracy jest  omówienie regulacji  aktywność TH  przy współudziale trzech głównych mechanizmów: 1) post-translacyjnego, z chwili na chwilę, poprzez fosforylację różnych miejsc w cząsteczce enzymu oraz 2) post-trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
(106 reference statements)
0
3
0
Order By: Relevance
“…The research was performed on patients with mild to moderate PD, moving independently similar to training processes on cyclergometers or treadmills [7,22,20,23]. Dance as an unconventional therapy method can serve as an effective way of improvement in individuals with PD, although only recently has it begun to be thoroughly researched and used in rehabilitation [17,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research was performed on patients with mild to moderate PD, moving independently similar to training processes on cyclergometers or treadmills [7,22,20,23]. Dance as an unconventional therapy method can serve as an effective way of improvement in individuals with PD, although only recently has it begun to be thoroughly researched and used in rehabilitation [17,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, intensive training processes cause biochemical changes in the CNS such as an increase in BDNF release, levels of antioxidant factors, a decrease in inflammatory factors and free radicals [7,20,30]. Research conducted on animal models of PD demonstrated that endurance training increased levels and activity of ty-rosine hydroxylase and dopamine concentrations in the extrapyramidal system [21,20]. The longterm training process resulted in a decrease in the heart rate of so-called resting bradycardia along with an increase in cardiac output capacity in patients with PD [22].…”
Section: Introductionmentioning
confidence: 99%
“…T also participates in the excitatory and inhibitory processes of sexual functions, modulating the activity of neurotransmitter systems, especially dopaminergic (Jordan et al, 2011a; Bell & Sisk, 2013) and opioid peptides (Sharp et al, 2022). Recently, it has been observed that T neurally‐produced increased dopamine signalling in the mesocorticolimbic system (Tomm et al, 2022) and in the extrapyramidal system (Przybylska et al, 2021).…”
Section: Androgensmentioning
confidence: 99%